Modeling, Analysis, and Control Design of a Single-Stage Boost Inverter - Md. Rasheduzzaman; Poria Fajri; Jonathan Kimball; Brad Deken (Energies, 2021)
A single-phase, single-stage, differential boost inverter comprises two independently-controlled boost DC-DC converters, with the load connected between their outputs. The net voltage on the load is sinusoidal and has a controllable frequency and magnitude that is larger than that of the DC source. The present work first derives steady-state and small-signal models of the inverter with parasitic elements. The results obtained from the line-to-output transfer function, control-to-output transfer function, open-loop input impedance, and open-loop output impedance models are compared with that of the ones obtained from the experimental testbed. Using the new models, a voltage mode controller is designed in the synchronous reference frame. The regulator design is explored through the use of an example. The results are verified against the small-signal model, then PLECS simulations, and finally a laboratory experiment. The results indicate excellent agreement between the model and experiment during transients in voltage reference, input source voltage, and output load. A sensitivity analysis is performed based on the inverter model considering the parameter variation. Finally, loss and efficiency estimations are provided in this work.